Decentralised facility-based training as an alternative model for SLMTA implementation: The Cameroon experience - Juliana Ndasi; Laura Dimite; Victor Mbome; Charles Awasom; Elive Ngale; Sidney Akuro; Ewane Leonard; Omotayo Bolu; Terrence Asong; Patrick Njukeng; Judith Shang (AOSIS, 2014)
Background:The Strengthening Laboratory Management Toward Accreditation (SLMTA) programme is designed to build institutional capacity to help strengthen the tiered laboratorysystem. Most countries implement the SLMTA three-workshop series using a centralised model, whereby participants from several laboratories travel to one location to be trained together. Objectives: We assessed the effectiveness and cost of conducting SLMTA training in adecentralised manner as compared to centralised training. Methods: SLMTA was implemented in five pilot laboratories in Cameroon between October 2010 and October 2012 by means of a series of workshops, laboratory improvement projects and on-site mentorship. The first workshop was conducted in the traditional centralised approach. The second and third workshops were decentralised, delivered on-site at each of the five enrolled laboratories. Progress was monitored by repeated audits using the Stepwise Laboratory Quality Improvement Process Towards Accreditation (SLIPTA) checklist. Results: Audit scores for all laboratories improved steadily through the course of the programme. Median improvement was 11 percentage points after the first (centralised) training and an additional 24 percentage points after the second (decentralised) training. Estimated per-laboratory cost of the two training models was approximately the same at US$21 000. However, in the decentralised model approximately five times as many staff members were trained, although it also required five times the amount of trainer time. Conclusion: Decentralised SLMTA training was effective in improving laboratory qualityand should be considered as an alternative to centralised training.